Brand Ambassadors and their Impact on Consumer Behavior: A Case Study of Mobile Companies in India - Aggarwal, S. S. (Indian Journal of Marketing, 2009)
A brand ambassador is a well-connected person or a celebrity who is used to promote and advertise a product or service. He/She is a diplomat, a representative of an organization, institution or corporation that best portrays the product or service. Brand ambassadors are the face and fingers of the brand; everything they touch, the brand is touching. Brand Ambassadors form the public image of brands and are the humans companies use to deliver their message to the public. Non-traditional marketing companies utilize Brand Ambassadors in campaigns to answer questions, engage the audience, and increase brand awareness. Using reputable firms to supply this type of staff allows companies to maintain a high quality of applicants that mirror the target demographic to reach consumers in the most effective manner.